2005
DOI: 10.21608/jvmr.2005.77976
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of some respiratory diseases among sheep and goats in Shalateen , Halaieb and Abu-Ramad Areas

Abstract: Nasopharyngeal swabs and pnuemonic lung autopsies collected from diseased or slaughtered sheep and goats suffering from respiratory manifestation were subjected to microbiological sreening. In addition, serum samples were collected from all animals were investigated. P. hemolytica was the most prevalent recovered bacterial isolates followed by S. aureus and E. coli. On the other hand, Aspergillus fumigatus was the most prevalent fungus. Aspergillus species and Candida albicans were also isolated. Most of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…The results of bacterial isolation in this study revealed the presence of various types of bacteria isolated from the affected lungs of small ruminants (Table 1). These findings were in partial agreement with Mahmoud et al (2005) who found that, the main bacterial isolates in sheep and goats were Staphylococcus aureus (12%), Strept. pneumoniae (4%), E. coli (8%), Pseud.…”
Section: Discussionsupporting
confidence: 91%
“…The results of bacterial isolation in this study revealed the presence of various types of bacteria isolated from the affected lungs of small ruminants (Table 1). These findings were in partial agreement with Mahmoud et al (2005) who found that, the main bacterial isolates in sheep and goats were Staphylococcus aureus (12%), Strept. pneumoniae (4%), E. coli (8%), Pseud.…”
Section: Discussionsupporting
confidence: 91%
“…were the main isolates from pneumonic lungs of camel, where the prevalence was high as 56% (Al-Rawashdeh et al, 2000); low as 1.07 and 2.85% (Tigani et al, 2007;Wareth et al, 2014, respectively) and may be very low as 0.04% (El-Deeb, 2015). Owing to P. multocida, the recovery rate from pneumonic lung lesions were 2.9% (Abo-Elnaga and Osman, 2012), 4.4% (Abubakar et al, 2010) and 10.7% (Chitgar et al, 2014), while M. haemolytica was 0.3% (Abubakar et al, 2010), 1.4% (Abo-Elnaga and Osman, 2012), 6.6% (Al-Tarazi, 2001) and 7.4% (Mahmoud et al, 2005).…”
Section: Advances In Animal Andmentioning
confidence: 99%
“…Pulmonary aspergillosis in sheep and goats is characterized clinically by apathy, anorexia, cough, dyspnea, and nasal discharge. 2,41 In goats, a nasal form of aspergillosis may occur, and is characterized by loss of condition associated with necrosis of the nasal mucosa and nasal turbinate bones, which may result in severe dyspnea. Cutaneous nodules, 0.3–3 cm diameter, occasionally ulcerated, may be observed in the dorsal nasal region and ears (Fig.…”
Section: Aspergillosismentioning
confidence: 99%
“…has been described occasionally in sheep and goats, preferentially in young, feedlot-confined animals. 25,41,42,46 The use of antimicrobials for prolonged periods, concomitant chronic diseases, and eating moldy feed are factors that have been implicated in pulmonary aspergillosis in ruminants. 41 Mastitis produced by Aspergillus spp.…”
Section: Etiology and Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation